UPAYA PATROLI RODA 2 SATUAN SAMAPTA UNTUK MENCEGAH TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN DI WILAYAH HUKUM POLRES KLATEN - TEGUH KRISANDI FARDHA (Police Studies Review, 2022)
The Samapta unit has the task of preventing criminal acts through preventive efforts. One of the preventive efforts is control, protection, escort, and patrol. Patrol is an effort to prevent disturbances of Public order and safety through police actions, this is regulated in Perkabaharkam Polri Number 1-2017th. In the Klaten Regency area, the crime of theft with weighteened been a disturbing crime. The crime of theft with weighteened is a challenge for the Klaten’s Police in creating Public order and safety. Therefore, in this study, the researcher wanted to explore how the 2-wheeled patrol efforts in preventing the crime of theft with weighteened and what actions were made to decrease the number of these crimes. This research was prepared using a qualitative approach and based on field research. In discussing the implementation and efforts of 2-wheeled patrols to prevent the crime of theft with weighteened, this study was analyzed using POAC theory, SWOT theory, and the concept of 2-wheeled patrol in accordance with Perkabaharkam Polri Number 1-2017th, concern to Patrol. The conclution from this project is the implementation and efforts of the 2-wheeled patrol unit of the Klaten’s Samapta unit were not maximized. This was analyzed by using the POAC and SWOT theory by finding that the use of 2-wheeled vehicles was not optimal, did not follow patrol’s SOP, lack of personnel, lack of education on personnel capacity development, the utilization of equipment is still neglected, and didn’t accordance to Perkabaharkam Polri Number 1-2017th.